Consumer Price Index and Economic Growth: A Case Study of Mauritania 1990 – 2013 - Mahmoud, Limam Ould Mohamed (Asian Journal of Empirical Research, 2015)
This study seeks to investigate the association between Consumer Price Index (CPI) and Gross Domestic Product (GDP) in Mauritania. An Empirical evidences are obtained from the Ordinary Least Square (OLS) and Granger Causality Test Model. The study utilizes time series data cover up the period from 1990 to 2013. Gross Domestic Product (GDP) was used as dependent variable, whereas Consumer Price Index (CPI) was used as independent variable. In order to check the stationarity of variables Augmented Dickey-Fuller Test (ADF) was employed. Result indicates that all variables found to be stationary at first difference at 5% level of significance. OLS Test revealed a positive and significant relationship between the GDP and CPI. Additional endeavour was made to verify the causal relationship between two variables by employing the Granger Causality Test. The result show unidirectional causality running from Inflation to economic growth. The most significant policy proposition of this outcome is that intensive exertion must be made by Mauritanian government to address the issues which are lead to an increase of price level (inflation) such as food and fuel crisis, exchange rate fluctuation, an increase in money supply, weak agriculture sector and so on.